(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
One of the most dreadful infectious viral disease that cause great economic losses for the poultry industry is the infectious bronchitis IB. The present study conducted to epidemiology and the molecular sequences of infectious bronchitis virus from broiler chickens’ fields in Nineveh governorate. The study covered seven regions around the Mosul city included (Al Msayed, Badoosh, Al?Qayara, Wanna, Basheeka, Al-shalalat , Al-hamdanya, and Bartalla) for the period extends from September 2022 to May 2023. The result recorded 16 suspected cases of IB. 14 of them have been diagnosed as IB virus by means of Polymerase Chain Reaction (Nested PCR). Most of the infections were in October and March, five cases of them were recorded in October, four cases in March, two conditions in September, and one case in other months of the study. (PCR), showed that the causative agent of IB in Al?Msayed, Badoosh, Al-Qayara, Wanna, Basheeka, Al shalalat , Al-hamdanya, and Bartalla) was from strain(AAS-IB01M Result showed a new strain which was submitted to the GenBank of the (NCBI) to be registered